The macroeconomic policy challenges of continued globalisation - Hervé, Karine (OECD Publishing, 2008)
This article investigates the macroeconomic policy challenges associated with a prospective continuation of international trade and financial integration over the next two decades, making use of a global macroeconomic model newly developed by the OECD. The analysis has several important policy implications. First, with the shares of non-OECD economies in world output, trade, and capital markets rising substantially, global economic developments would become much more dependent on developments in these economies than they used to be. Second, the sustainability of existing global current account imbalances will depend in part on the future build-up and composition of international assets and liabilities. While the imbalances could be sustainable for some time if economic integration continues at its current pace, a slowdown of the globalisation process would raise the likelihood of a disruptive adjustment in financial markets. Third, the increase in trade and financial linkages implies that macroeconomic shocks in a given country or region have a larger impact on other economies in the future than they do today. Policymakers in the OECD may have to act more promptly and more vigorously to economic "shocks" in the non-OECD economies in order to limit the impact on OECD economies
Keywords: Economics